Identification of candidate genes expressions and polymorphisms associated with atherosclerosis from postmortem cases in Hospital Kuala Lumpur and Hospital Serdang, Malaysia - Blin, Joan (2013)
Atherosclerosis as presented by coronary artery disease is a slow progressing, pathological process of plaque formations within arteries. Differential expression of susceptibility genes plays important role in the pathogenesis of atherosclerosis. This study aimed to determine differential expression of 11 candidate genes and polymorphisms associated with atherosclerosis from postmortem cases in Hospital Kuala Lumpur and Hospital Serdang. Seventy six atherosclerotic coronary artery tissues (ACAT) (cases) and 149 non-atherosclerotic coronary artery tissues (NCAT) (healthy controls) were gathered from the Forensic Department of Hospital Kuala Lumpur and Hospital Serdang based on predetermined inclusion and exclusion criteria. Gross examination findings showed the presence of mild to severe atheroma in ACAT samples, whereas NCAT samples showed clean tissues. Microscopic findings of ACAT samples showed presence of both stable (80.3%) and unstable atheroma (19.7%) respectively, with 11.8% of the samples were superimposed with thrombosis. Six RNA samples of each ACAT and NCAT were analyzed using GenomeLab Genetic Analysis System (GeXP). Student’s t-test showed significant increase in expression levels of low density lipoprotein receptor (LDLR), tumor protein 53 (TP53), and matrix metalloproteinase 9 (MMP9) genes in ACAT samples (p< 0.05). No significant differences in the expression levels were obtained for the remaining eight candidate genes. Restriction fragment length polymorphism (RFLP) analysis was performed on 76 ACAT and 149 NCAT samples to investigate the variation in LDLR (C88S), TP53 (TP53 codon 72), and MMP9 (MMP9-1562C>T) genotypes. Descriptive statistics were used to determine genotypes distribution of each polymorphism in both groups. The Chi-square (χ2) test revealed significant differences in CT genotype and T allele of MMP9-1562C>T polymorphism when compared between the ACAT and NCAT groups (CT: χ2= 19.758, df= 1, p= 0.000 and T allele: χ2 = 21.109, df= 1, p=0.000). The CT genotype and the T allele were significantly higher in ACAT samples (CT: 57.9% in ACAT vs. 27.5% in NCAT and T allele: 77.9% in ACAT vs. 48.3% in NCAT). There were positive associations of CT genotype and T allele with atherosclerosis (CT: OR= 3.622, 95% CI= 2.028 – 6.470 and T allele: OR= 3.780, 95% CI= 0.2115 – 6.755). There were no significant differences of CT genotype and T allele distribution among the three major ethnicities and between genders of the healthy population. No significant associations were identified in the C88S and TP53 codon 72 polymorphisms with regard to atherosclerosis risk. In conclusion, CT genotype and T allele of the MMP9- 1562C>T polymorphism displayed associations with the risk of developing atherosclerosis from postmortem cases in Hospital Kuala Lumpur and Hospital Serdang.